Pengembangan Sistem Pengukuran Kinerja, Akuntabilitas Kinerja Dan Penggunaan Informasi Kinerja Di Pemerintah Daerah: Perspektif Isomorfisma Institutional - Herlina Primarisanti; Rusdi Akbar (Jurnal Solusi, 2018)
This study aims to explore the development of performance measurement, performance accountability, and the use of performance information in the Local Government using the qualitative theory of institutional isomorphism. The theory of institutional isomorphism is used to interpret and explain the phenomenon of coercive, mimetic and normative isomorphism in the development of performance measurement systems, performance accountability and use of performance information. This research is a qualitative research using semi-structured and open interviews. Qualitative data analysis in this study uses thematic analysis. The results of this study indicate that the three phenomena of institutional isomorphism (coercive, mimetic and normative) are found in the process of developing a system of performance measurement, performance accountability, and the use of performance information in the Regional Government